Quantifying an Upper Extremity Everyday Task With 3D Kinematic Analysis in People With Spinal Cord Injury and Non-disabled Controls - Lili, Lamprini; Sunnerhagen, Katharina S.; Rekand, Tiina; Alt Murphy, Margit (Frontiers in Neurology, 2021)
Objectives: Upper extremity function after spinal cord injury (SCI) is an important factor for performance of activities of daily living. An objective assessment of upper extremity function preferably in purposeful daily tasks is essential in understanding its impact on real-life activities. This study aimed to identify which movement parameters of upper extremity, measured by kinematic analysis during a purposeful daily task, are impaired in people with cervical or thoracic SCI. Materials and Methods: The study included 29 adults (mean 59.5 years, 9 women and 20 men) with cervical (n = 19) or thoracic (n = 10) established complete (n = 15) or incomplete (n = 14) SCI, and 54 non-disabled controls with commensurable age and sex (mean 59 years, 15 women, 39 men). The 3D kinematic data were captured with a five-camera system during a standardized unilateral daily task (drinking from a glass). In SCI, the upper extremity functioning of each arm was assessed with Action Research Arm Test (ARAT). Having a full score in ARAT indicated full functioning; a score of <57 points indicated limited functioning. Kinematic data from full functioning arms (n = 27) and limited functioning arms (n = 30) in SCI were compared with the non-dominant arms (n = 54) in controls. Results: In the limited upper extremity functioning group, movement time, smoothness, arm abduction, wrist angle, trunk displacement, and inter-joint coordination, but not peak velocity of the hand, angular velocity of elbow, and relative time to peak velocity, all differed from controls. In the full upper extremity functioning group, arm abduction alone was significantly different from controls. Conclusions: The findings demonstrate that apart from measures of peak velocity, kinematic measures of movement quality including movement time, smoothness, trunk displacement, and joint angles are impaired in people with limited upper extremity functioning after SCI. The study provides robust results applicable to a representative population of individuals with established cervical or thoracic SCI. The results suggest that kinematic analysis might be useful for those with limited functioning in order to get a better understanding of the specific movement impairments in daily tasks after SCI.